WEDDING CENTER DENGAN PENDEKATAN INTANGIBLE METAPHOR DI SURAKARTA - Wulan Cahyaning Maharani; Suparno Suparno; Ummul Mustaqimah (ARSITEKTURA, 2016)
Nowadays, the number of marriage and wedding expo especially in Surakarta is increasing. At the other hand, the facility to support such events in Surakarta is not sufficient. Beside that, people are now forgetting the traditional values and norm because of they think it's outdated. The purpose of this design is to build a building which has complete facility to support preparation and the wedding event itself and has a philosophy, called lingga yoni. Lingga yoni means the unity between man and woman. But, the problem is how to translate this intangible philosophy lingga yoni to a building that support planning and wedding event itself. The methods used is architectural method to solve the problems. The result is a wedding center design that accommodate everything that needed to prepare and held a wedding ceremony. It means it contain several services from information to consultation for wedding. Everything that related to wedding is gathered in one building with modern system, one stop service. So the customers can held their wedding efficiently and effectively. The building also shows lingga yoni philosophy beautifully, that shows wedding its nobility and sacred to the the brides and the guests.